Effects of nano zeolite-coated fertilizer and cow boneon the growth and N uptake of maize in inceptisol of Patuk, Gunung Kidul - Khairul Anwar; Sri Nuryani Hidayah Utami; Makruf Nurudin (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2022)
Nanotechnology is a science that deals with objects measuring 1-100 nm that are different from their original properties. Nano-technology fertilizers are more reactive and on target with minimum use. Nanotechnology fertilizers can be utilized as slow-release fertilizers, allowing for optimum fertilizer uptake by plants. Because of the holes that can store nitrogen fertilizers, zeolite and bovine bone can be utilized as fertilizer coatings. This study was conducted at Universitas Gadjah Mada's Faculty of Agriculture. The research method used was a 2X5 factorial completely randomized design (CRD) with each treatment being repeated 3 times so that the total polybags used were 30 polybags. The first factor was the type of coating material for urea, nano zeolite, and nano bovine bone. The second factor consisted of a dose of coated urea fertilizer with five kinds of dose treatments, which were 0, 100, 200, 300, and 400kg.ha-1. ANOVA was used to analyze parameter data, followed by testing using the DMRT (Duncan's Multiple Range Test). When compared to nano bovine bone, the effectiveness of N removal with nano zeolite generated the best results as a slow-release fertilizer on N uptake. The best N fertilization dose with nano zeolite coating was 200 kg.ha-1, which increased corn plant growth by producing the highest plant height (167.17 cm) and N uptake of 1.6 g/plant. This research can be a recommendation for more effective and efficient Nitrogen fertilization for corn farmers.